Making rhetoric a reality: inclusion in practice as "transformative learning". Issue 2 (9th May 2016) - Mercer, Dave; Kenworthy, Heidi; Pierce-Hayes, Ian
Abstract : Purpose: – "Inclusivity" and "empowerment" are central concepts in the philosophy of nursing practice and education. Recent professional concern has focused on the need to embed compassion in healthcare cultures where practice contributes to learning. The purpose of this paper is to explore an innovative partnership approach to undergraduate placement provision for adult-general nursing students in the context of learning disability and mental health. Design/methodology/approach: – Critical discussion focuses on evaluation of a non-clinical placement centred on the health and social care of individuals with a learning disability or mental health needs. Two projects from practice around healthy living and hate crime illustrated the value of transformative learning as a pedagogic philosophy. Findings: – Student feedback offered insight into social and cultural processes that impact on practice-based learning, and factors promoting inclusive engagement. Such included the context of identity formation, narrative as an evidence-base for caring, and personal/emotional growth through critical reflection. Practical implications: – Evaluation provided a platform to re-think model(s) of clinical practice learning in healthcare education derived from a non-clinical placement. There are tangible benefits for sustaining value-led practice at a time of political change in the way health services are configured and delivered. Social implications: – When engagement with the principles of inclusivity and empowerment become part of the lived-experience of the nursing student, longer-term recognition and retention of caring, and enabling values are more likely to endure. Originality/value: – The emotional development and skills acquired by nursing students transfer to all branches of the profession by revitalising core conditions of compassion, respect, dignity, and humanity.